The Impacts of financialization on the finance-investment-saving-funding circuit - Santos, Diogo; da Cunha Resende, Marco Flávio (Brazilian Keynesian Review, 2022)
The objective of this work is to evaluate the effects of the financialization of contemporary capitalism on the post-Keynesian finance-investment-saving-funding (FISF) circuit from a systematization of the main evidences brought by the literature on financialization. For this, a presentation of the FISF circuit is carried out and then the impacts of financialization on each of its components are investigated. It is concluded that despite some positive effects, all circuit elements are negatively impacted. However, it is in the funding component that the greatest effects of financialization on the circuit are concentrated. These impacts have consequences on the financial stability of the economy, economic growth and the role of the State.